2015
DOI: 10.1080/10426914.2015.1059443
|View full text |Cite
|
Sign up to set email alerts
|

Water-Repellent Approaches for 3-D Printed Internal Passages

Abstract: In this work, two different manufacturing approaches are presented that create waterrepellency (hydrophobicity and super-hydrophobicity) for acrylonitrile butadiene styrene (ABS) structures. In particular, this is the first study to render .three-dimensional (3D) printed ABS surfaces with internal flow paths to be superhydrophobic. The first approach uses standard wet-based chemical processing for surface preparation after which a fluorocarbon layer is deposited by dip coating or with vapor deposition. This fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…In particular, 3D printers based on fused filament fabrication (FFF) technology are one of the most accessible and simplest options [ 8 ]. They are open-source, low-cost machines which usually use thermoplastic materials [ 9 , 10 ] and can easily be modified to improve the quality of the printed 3D products [ 11 ]. A variety of biocompatible polymers can be used for scaffold production with FFF.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, 3D printers based on fused filament fabrication (FFF) technology are one of the most accessible and simplest options [ 8 ]. They are open-source, low-cost machines which usually use thermoplastic materials [ 9 , 10 ] and can easily be modified to improve the quality of the printed 3D products [ 11 ]. A variety of biocompatible polymers can be used for scaffold production with FFF.…”
Section: Introductionmentioning
confidence: 99%
“…However, the dry weight of scaffolds linearly increased from 2.22 mg, 3.60 mg, 6.10 mg, and 8.97 mg, to 9.73 mg for the scaffolds with infill density of 10%, 20%, 30%, 40%, and 50%, respectively (p < 0.05) ( Figure 2C). Studies have demonstrated that the porosity and pore size are some of the most significant characteristics of 3D printed scaffolds in tissue engineering [26][27][28][29][30][31][32]. In fact, scaffolds with adequate pore size and porosity provide a suitable microenvironment for sufficient cell-cell interaction and cell migration, proliferation, and differentiation [29].…”
Section: Properties Of Ia3dmentioning
confidence: 99%
“…Dip-transfer [36], is another method combines a 3D printed mould to create mushroom-shaped PU pillars, dipping them in PU and placed on an etched mould to create the second (and smaller) hairs. Some techniques were also applied for fabrication of micro features, Milionis et al [37] investigated different manufacturing approaches to create water-repellency and functionalize the surfaces of 3-D printed heat exchangers fabricated from acrylonitrile butadiene styrene (ABS). The structures were printed linear with a commercial Fused Deposition Modeling (FDM) 3D printer with the resolution about 100 µm.…”
Section: Scope and Aimmentioning
confidence: 99%